Literature as History of Rural Andalusian Women: The Case ofHijas de un sueño[Daughters of a Dream] (2018)
My first short story collection, Hijas de un sueño [Daughters of the Dream] was published in November 2017. In this book I open the doors of Candiles, an imaginary rural town located somewhere in Eastern Andalusia. Its protagonists are rural women who seek to step out of their anonymity and leave their imprint on an alternative History. The challenge of this study is to position myself as a feminist literary critic, so as to prove that my location in the South of Spain is not free of ideology, as reflected in my creative writing. While I demand a socio-cultural specificity for Candiles, the universal transcendence of its geographical limits ultimately takes a stance for a regionalist, ethnic, sexual and class anti-essential - ism that allows me to create complex and empowered characters. Taking concepts such as ‘hegemony,’ ‘common sense,’ or ‘ideology’ as a starting point, I agree with Ania Loomba that there is a possibility to explore a subversive space within the dominant ideology, and I adhere to her redefinition of colonialism, linked to outdated nationalisms, existing even among Western countries or inside the regions of the same country. I thus understand my writing as a reflection of Southern subalternity. My case study will be the short story ‘Twelve butterflies’ (‘Doce mariposas’), where I make up a legend for Candiles, vaguely located in the 19th century. The geographical and historical subalternity of Andalusia, biological essen - tialism in ‘feminine literature’, and gender violence as linked to the strategic use of legends, fairy tales and palimpsest, will lead to the proposal of an alternative History for Andalusian women beyond the false historical objectivity of patriarchy.